Dampak Pandemi Covid-19 Terhadap Kondisi Ekonomi Pedagang Olahan Hasil Laut di Kecamatan Bulak, Surabaya - Susilowati, Mei; Winarno, Sri Tjondro; Yektiningsih, Endang (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
This study aims to know the impact of the Covid-19 pandemic on processed fisheries' sellers' economic conditions in Bulak District, Surabaya City. The data collection technique was done by observing, interviewing, and documenting. This research was conducted from March until April 2021. The method of analysis in this study is quantitative descriptive analysis. The data were analyzed using the Wilcoxon Signed-Rank. This study indicates that the Covid-19 pandemic affects the economic conditions of processed fisheries' sellers in Bulak District, Surabaya City. A significant value can prove this effect in the test results < 0.05, which means a substantial difference in the outpouring of working time, capital, income, and household consumption of processed fisheries' sellers before and after the Covid-19 pandemic.